Sosialisasi Penanggulangan Kenakalan Remaja: Disiplin Berlalu Lintas - Sidabutar, Sadat N S; Annisa Zulfa Safira (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Socialization of Juvenile Delinquency Prevention: Traffic Discipline One of the traffic problems is juvenile delinquency which is often caused by, for example, not having a driver’s license, using the noisy motorbike exhaust, speeding on the road and so on. Traffic violations have a direct negative impact on the Security, Safety, Order and Smoothness of Traffic and Road Transportation sectors.This is a problem faced by society which is now increasingly widespread. The method used for the 2nd grade at Senior High School 3 Sepaku to overcome juvenile delinquency in traffic discipline are the methods of socialization, lectures and discussions. The success of this socialization was due to the enthusiasm of students to know and understand aspects of criminal law, especially traffic violations by teenagers.